Penerapan Metode Amtsilati dalam Mengatasi Kesulitan Membaca Kitab Kuning di Kelas 3 C Diniyah di Pondok Pesantren Hidayatul Mubtadiin Desa Sidoharjo Kecamatan Jati Agung - Arina Manasikana (Journal on Education, 2024)
This study aims to determine how the application of the Amtsilati method in overcoming difficulties in reading yellow books in class C diniyah at the Hidayatul Mubtadiin Islamic boarding school, Sidoharjo village, Jati Agung district, South Lampung Regency in the 2023/2024 academic year and to determine the supporting and inhibiting factors in the application of the Amtsilati method in overcoming difficulties in reading yellow books in class 3 C diniyah at the Hidayatul Mubtadiin Islamic boarding school. This research is a Qualitative Research, the type of research is descriptive qualitative with data collection techniques in this study through observation, interviews, and documentation. This research was conducted at the Hidayatul Mubtadiin Islamic boarding school with the data sources that I used in interviews with 4 informants, namely 1 Ustadz, 2 ustadzah and 1 female student in class 3 C diniyah Amtsilati class, Hidayatul Mubtadiin Islamic Boarding School, Jati Agung. The results of this study indicate that the application of the Amtsilati method in overcoming the difficulty of reading the yellow book has been carried out well, and has brought about changes in studying the yellow book. By implementing the Amtsilati method in class 3 C diniyah, it makes it easier for students to read the yellow book. In the application of the Amtsilati method, there are 3 activity sessions, namely the Opening Stage, the ustadz and students read hadloroh together followed by reading Surah Alfatihah. The second is the delivery of material using classical techniques. And the third activity is the Closing Stage, namely praying together. The supporting factors for the Implementation of the Amtsilati method are the ustadz delivering the material with enthusiasm, there is no element of coercion and getting approval from the kyai to apply the Amtsilati method. The inhibiting factors for the Implementation of the Amtsilati Method are the lack of time allocation and the lack of concentration of students during learning.